Complex approach to monitoring athletes in the scope of overtraining prevention - Bernaciková, Martina; Novotný, Jan; Burešová, Iva; Žákovská, Alena (Studia Sportiva, 2019)
The article introduces the issue of monitoring intensively training athletes who wish to avoid overtrai-ning and want their training to be as effective as possible. The current definitions of overreaching and overtraining are addressed, together with the summary of causes, development and prevention of such conditions. The focus of the article is on the overview of relevant diagnostic methods including the latest non-invasive biochemical methods. The complex approach to the selection of psychological and physiological methods to establish the degree of the internal load of athletes is emphasised. A three--degree concept of athlete monitoring according to the demandingness and periodicity of diagnostic methods usage is presented.
Keywords: syndrom přetrénování; Overtraining Syndrome; Athletes; Humans; sportovci; tělesná námaha; Physical Exertion; Athletic Performance; sportovní výkon; přetrénování; Fatigue; diagnostické techniky a postupy; únava; syndrom; Syndrome; psychologické testy; Psychological Tests; monitorování fyziologických funkcí; Diagnostic Techniques and Procedures; Heart Rate; Monitoring, Physiologic; lidé; srdeční frekvence